(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Negotiating skills are not part of the traditional lawyer’s training. Today, however, new problem-solving skills are required of the lawyer to settle disputes consensually before trial. This article outlines the methodology for a pilot study that investigates the cooperative problem-solving skills development through neuroscientific devices that are non-invasive, portable and therefore usable in ecological contexts. The use of Brain-Computer-Interface would allow trained negotiators to explicitly develop neuro-cognitive tools, with greater interaction between intuitive and analytical thinking systems.